Best sellers in economy, a reading from the perspective of economic geography. Implications for the landscape, environment and spatial planning - Marchena-Gómez, Manuel Jesús (Revista de Estudios Andaluces, 2015)
In this paper, from the bestselling books and ideas, manifestos and their lessons on International Economic Geography are used. Stock is taken of the Contributions of the so-called New Economic Geography and Their Relationship with The best sellers in economy. Attempts Have Been Made to highlight the innovations and updates in Economic Geography Encouraged by authors in vogue in economy. After using a selection method taking into account criteria of electronic sale and media interest, three of them have been chosen due to their influence and subject of interest for Economic Geography on a scale global. Finally, have been conclusions drawn about the environment, the landscape and the spatial planning. In any case, there is a common denominator in the reading of These texts: the growing role of territorial and social Inequalities in the world, The Importance of the institutional quality In Their interpretation and, in general the need for communication Between social sciences to Understand what happens, beyond the formally sophisticated and unreal apparatus of an economistic nature Which are Considered wrongly scientific objects in themselves.